Monitoring Saccharomyces cerevisiae populations by mtDNA restriction analysis and other molecular typing methods during spontaneous fermentation for production of the artisanal cachaça - Araújo,Roberta A.C. (2007)
An ecological study on Saccharomyces cerevisiae populations in spontaneous fermentation has been conducted in three vats of a cachaça distillery in Minas Gerais, Brazil. Ninety-seven yeast isolates were collected at the beginning, the middle and at the end of the production period, and were identified by standard methods. Differentiation between the indigenous S. cerevisiae strains isolated was performed by mitochondrial DNA (mtDNA) restriction analysis, RAPD-PCR, and PCR fingerprint using an intron splice primer. Analysis of the mtDNA restriction profiles revealed 12 different patterns, 11 corresponding to indigenous yeasts (I to XI) and one (XII) to a commercial strain of the bakery yeast. Pattern II (53.6% of the population) and pattern IV strains were present in all the vats. Pattern IV strain raised from the middle to the end of the period reaching proportions near those of pattern II strain. PCR methods allowed the differentiation of 41 molecular profiles. Both methods showed population fluctuation of S. cerevisiae strains along the period of cachaça production and among different vats of the distillery.